Development of a standardized patient-reported clinical questionnaire for children with spinal pain - Freja Gomez Overgaard; Henrik Hein Lauridsen; Mads Damkjær; Anne Reffsøe Ebbesen; Lise Hestbæk; Mikkel Brunsgaard Konner; Søren Francis Dyhrberg O’Neill; Stine Haugaard Pape; Michael Skovdal Rathleff; Christian Lund Straszek; Casper Nim (BMC Medical Research Methodology, 2025)
Abstract Background Spinal pain affects up to 30% of school-age children and can interfere with various aspects of daily life, such as school attendance, physical function, and social life. Current assessment tools often rely on parental reporting which limits our understanding of how each child is affected by their pain. This study aimed to address this gap by developing MySpineData-Kids (“MiRD-Kids”), a tailored patient-reported questionnaire focusing on children with spinal pain in secondary care (Danish hospital setting). Methods The process and development of MiRD-Kids followed a structured, multi-phase approach targeted children in outpatient care. The first phase involved evidence-synthesis, expert consultations, and item formulation, resulting in the first version. The second phase involved pilot testing among pediatric spinal pain patients, leading to modifications for improved clarity and relevance. The third phase involved implementation at the Pediatric outpatient track at The Spine Centre of Southern Denmark, University Hospital of Southern Denmark. Results MiRD-Kids was based on selected items from seven questionnaires, encompassing 20 items across six domains. Pilot testing with 13 pediatric patients facilitated modifications and finalized the questionnaire. The questionnaire includes sections for parents/legal guardians and six domains for children covering pain, sleep, activities, trauma, concerns, and treatment, following the International Classification of Functioning, Disability, and Health (ICF). Implementation challenges were overcome within a 2-month period, resulting in the clinical questionnaire MiRD-Kids a comprehensive tool for assessing pediatric spinal pain in hospital outpatient settings. Conclusion MiRD-Kids is the first comprehensive questionnaire for children with spinal pain seen in outpatient caresetting and follows the ICF approach. It can support age-specific high-quality research and comprehensive clinical assessment of children aged 12 to 17 years, potentially, contributing to efforts aimed at mitigating the long-term consequences of spinal pain.